The Influence of Dietary Salt on the Osseointegration of Implants in Aging Rats - Baldisserotto, Julio; Padilha, Dalva Maria Pereira; Amenábar, José Miguel (International Archives of Otorhinolaryngology, 2019)
Introduction The bone-implant interface has been studied extensively, but only few papers focused on the nutritional aspects that may affect bone quality, especially salt intake.Objective To study the osseointegration of implants in salt-loaded rats with low mineral bone content.Methods A total of 60 4-month-old male rats were divided in 2 groups (n = 30), being these groups divided in 2 periods, (2 and 4 months). The control group received a normal diet, while the test group received a diet supplemented with 1% sodium chloride (NaCl). Implants were placed in the tibia of both groups. A total of 15 animals of each group were sacrificed at the 2nd month of the experiment, while the remaining animals were sacrificed at the 4th month.Results No statistically significant difference was found in food intake between the groups on any experimental period, but a statistically significant difference was found in the liquid intake in the saline group in both periods. For all groups, osseointegration was observed in both groups. The mean percentage of osseointegration in the cortical bone, in the trabecular bone, and in the total osseointegrated surface between the control (46.38 ± 16.17%) and saline (49.13 ± 11.52%) groups at 2 months was not statistically different (p = 0.61). The total osseointegration areas of the control (53.98 ± 12.06%) and saline (51.40 ± 13.01%) groups at the 4th month of the study were not statistically (p = 0.61).Conclusion Ingestion of salt did not affect directly the osseointegration process during the period of the experiment. The results suggest that mineral losses may not affect the achievement of good osseointegration in aging rats.
Keywords: osseointegration; sodium chloride; bone density; bone-implant interface